1995
DOI: 10.1074/jbc.270.16.9207
|View full text |Cite
|
Sign up to set email alerts
|

The Disulfide Folding Pathway of Human Epidermal Growth Factor

Abstract: Human epidermal growth factor (EGF) contains three disulfides and 53 amino acids. Reduced/denatured EGF refolds spontaneously in vitro to acquire its native structure. The mechanism of this folding process has been elucidated by structural analysis of both acid and iodoacetate trapped intermediates. The results reveal that the folding is accompanied by a sequential flow of unfolded EGF (0-disulfide) through three groups of folding intermediates, namely 1-disulfide, 2-disulfide, and 3-disulfide (scrambled) EGF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
67
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(70 citation statements)
references
References 28 publications
3
67
0
Order By: Relevance
“…It has been reported that cysteine has a higher redox potential than glutathione [25,26]. Results published by Chang et al [27] demonstrated that the use of cysteine increased not only the rate at which hEGF was refolded but also its yield [13,27]. Refolding of our recombinant E5/K5-coil-EGF in the presence of cysteine resulted in an approximately 20% yield after purification ( Table 1), confirming that cysteine improves refolding of coiltagged EGF, as well as untagged EGF.…”
Section: Discussionsupporting
confidence: 73%
“…It has been reported that cysteine has a higher redox potential than glutathione [25,26]. Results published by Chang et al [27] demonstrated that the use of cysteine increased not only the rate at which hEGF was refolded but also its yield [13,27]. Refolding of our recombinant E5/K5-coil-EGF in the presence of cysteine resulted in an approximately 20% yield after purification ( Table 1), confirming that cysteine improves refolding of coiltagged EGF, as well as untagged EGF.…”
Section: Discussionsupporting
confidence: 73%
“…). This native-like 2-disulfide species was shown to accumulate rapidly along the folding pathway of EGF (11). But unlike BPTI, the major 1-disulfide intermediates of EGF were shown to contain both non-native and native disulfide bonds (11,22).…”
Section: Discussionmentioning
confidence: 99%
“…But unlike BPTI, the major 1-disulfide intermediates of EGF were shown to contain both non-native and native disulfide bonds (11,22). Moreover, scrambled 3-disulfide species were found along the folding pathway of EGF (11), which is characteristic of the folding of hirudin and PCI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the formation of disulfide bonds could be used as a useful tool in probing the protein-folding pathway (30). The folding pathways of many proteins, such as bovine pancreatic trypsin inhibitor (31)(32)(33)(34)(35), ribonuclease A (36 -38), epidermal growth factor (39,40) have been widely studied by using this method. Several members of the insulin superfamily have been identified, including insulin, IGF-I (41), IGF-II (42), relaxin HI (43), amphioxus insulin-like peptide (44), prothoracicotrophic hormone-II (45), molluscan insulinrelated peptide (46), Caenorhabditis elegans insulin-like peptide (47), etc.…”
mentioning
confidence: 99%